Tin(II)-EDTA complex: kinetic of thermal decomposition by non-isothermal procedures - Guinesi, L. S.; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Veronezi, A. M. (Elsevier B.V., 2004)
Tin on the oxide form, alone or doped with others metals, has been extensively used as gas sensor, thus, this work reports on the preparation and kinetic parameters regarding the thermal decomposition of Sn(II)-ethylenediaminetetraacetate as precursor to SnO2. Thus, the acquaintance with the kinetic model regarding the thermal decomposition of the tin complex may leave the door open to foresee, whether it is possible to get thin film of SnO2 using Sn(II)-EDTA as precursor besides the influence of dopants added.The Sn(II)-EDTA soluble complex was prepared in aqueous medium by adding of tin(II) chloride acid solution to equimolar amount of ammonium salt from EDTA under N-2 atmosphere and temperature of 50degreesC arising the pH similar to 4. The compound was crystallized in ethanol at low-temperature and filtered to eliminate the chloride ions, obtaining the heptacoordinated chelate with the composition H2SnH2O(CH2N(CH2COO)(2))(2).0.5H(2)O.Results from TG, DTG and DSC curves under inert and oxidizing atmospheres indicate the presence of water coordinated to the metal and that the ethylenediamine fraction is thermally more stable than carboxylate groups. The final residue from thermal decomposition was the SnO2 characterized by X-ray as a tetragonal rutile phase.Applying the isoconversional Wall-Flynn-Ozawa method on the DSC curves, average activation energy: E-a = 183.7 +/- 12.7 and 218.9 +/- 2.1 kJ mol(-1), and pre-exponential factor: log A = 18.85 +/- 0.27 and 19.10 +/- 0.27 min(-1), at 95% confidence level, could be obtained, regarding the loss of coordinated water and thermal decomposition of the carboxylate groups, respectively. The E-a and logA also could be obtained applying isoconventional Wall-Flynn method on the TG curves.From E-a and log A values, Dollimore and Malek procedures could be applied suggesting R3 (contracting volume) and SB (two-parameter model) as the kinetic model to the loss of coordinated water (177-244degreesC) and thermal decomposition of the carboxylate groups (283-315degreesC), respectively. Simulated and experimental normalized DTG and DSC curves besides analysis of residuals check these kinetic models. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Sn(II)-EDTA; non-isothernial kinetics; activation energy; kinetic model